Modeling the Growth and Interaction Between Brochothrix thermosphacta, Pseudomonas spp., and Leuconostoc gelidum in Minced Pork Samples - Cauchie, Emilie; Delhalle, Laurent; Baré, Ghislain; Tahiri, Assia; Taminiau, Bernard; Korsak, Nicolas; Burteau, Sophie; Fall, Papa Abdoulaye; Farnir, Frédéric; Daube, Georges (Frontiers in Microbiology, 2020)
The aim of this study was to obtain the growth parameters of specific spoilage micro-organisms previously isolated in minced pork meat samples, and to develop a three-spoilage species interaction model under different storage conditions. Naturally contaminated samples were used to validate this approach by considering the effect of the food microbiota. Three groups of bacteria were inoculated on irradiated samples, in mono- and in co-culture experiments (n = 1152): Brochothrix thermosphacta, Leuconostoc gelidum and Pseudomonas spp. (Pseudomonas fluorescens and Pseudomonas fragi). Samples were stored in two food packaging (food wrap and modified atmosphere packaging (CO2 30% / O2 70%)) at isothermal conditions (4°C, 8°C and 12°C). Analysis were carried out by using both 16S rRNA gene amplicon sequencing and classical microbiology in order to obtain bacterial abundance during the storage period. Growth parameters were obtained by fitting primary (Baranyi) and secondary (square root) models. The food packaging shows the highest impact on bacterial growth rates, which in turn have the strongest influence on the shelf life of food products. Based on these results, a three-spoilage species interaction model was developed by using the modified Jameson-effect model and the Lotka Volterra (prey-predator) model. The Lotka Volterra model shows good fit indexes (RrMSE and R2). But the modified Jameson-effect model showed slightly better performances, with 40 – 86% out of the observed counts failing into the Acceptable Simulation Zone. These results were then compared with an independent validation dataset. But more datasets are probably needed to obtained reliable factors, and so better model fittings, especially for a three- or more-spoilage species interaction models. Further studies are also needed to better understand the dynamics of spoilage bacteria towards each other and in the presence of natural microflora.